Urban Sufism in West Java: Reclaiming Spiritual Identity through Qadiriyya-Naqshbandiyya Practices in the Digital Era - Wasik, Abdul; Setiawan, Cucu; Sidik, Mohamad Dindin Hamam (Tashwirul Afkar, 2024)
This study aims to analyse the engagement of urban Muslim youth in the practices of the Qadiriyya-Naqshbandiyya Sufi order as a spiritual response to identity crises, cultural dislocation, and the pressures of contemporary digital life. The primary focus is directed towards exploring the contribution of collective Sufi practices-such as dhikr, suluk (spiritual retreat), and classical Islamic text study-to spiritual restoration and the reconstruction of religious identity in urban areas of West Java. A qualitative approach was employed, with data collected through in-depth interviews, participatory observation, and thematic analysis of the empirical experiences of Sufi community members. Three key findings were identified: (1) traditional spirituality contributes to strengthening psychological resilience and deepening the search for existential meaning; (2) the Sufi order functions as an inclusive and emotionally supportive social space that reinforces collective identity across social classes; and (3) Sufi practices demonstrate a symbolic resistance to ideological purification through reflective, affective, and locally grounded approaches. The findings indicate that Sufi communities possess the potential to act as cultural and spiritual agents in shaping a moderate religious habitus among youth. The originality of this research lies in its integration of tradition, technology, and transcendence in explaining the dynamics of Muslim youth religiosity in the postmodern era, as well as its contribution to offering a new conceptual framework in the study of urban Sufism and the formation of religious identity.